FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DI KALIMANTAN TIMUR - Nabila Primadona (2022)
High economic growth is one of the goals of economic development. A region's progress can be measured by how fast its economy is growing. One way to figure out how far a region's economy has come is to look at how often the economy grows. Investing can increase the amount of technology and other capital goods that are available, as well as the number of workers. This is because as the population grows, so does the quality of the workforce in terms of skills and education. The goal of this study was to find out how domestic investment, foreign investment, the labor force participation rate, the district/city minimum wage, and the human development index affect East Kalimantan's gross regional domestic product. As many as 110 data were used from 2011 to 2021 for the sample. For this quantitative analysis, econometric tools include Eviews 9, which uses multiple linear regression analysis with panel data. The Central Statistics Agency of East Kalimantan and the National Single Window for Investment both put out reports that were used to gather the data. The results showed that (1) Domestic Investment didn't make much of a difference to East Kalimantan's Gross Regional Domestic Product. (2) The effect of foreign investment on East Kalimantan's gross domestic product was not very big. (3) The number of people working didn't have much of an effect on East Kalimantan's GDP. Gross Regional (4) The Regency/City Minimum Wage has a big impact on East Kalimantan's Gross Regional Domestic Product (GRDP). (5) The Human Development Index has no big effect on the Gross Regional Domestic Product of East Kalimantan. Domestic Investment, Foreign Investment, the Labor Force Participation Rate, the District/City Minimum Wage, and the Human Development Index do not have a big effect on East Kalimantan's Gross Regional Domestic Product (GRDP). Keywords: Domestic Investment, Foreign Investment, Labor Force Participation Rate, District/City Minimum Wage and Human Development Index, Gross Regional Domestic Product in East Kalimantan